PEMANFAATAN PELET KULIT JENGKOL (Pihecellobium Lobatum Benth) DALAM RANSUM DOMBA DAN PENGARUHNYA TERHADAP PH DAN TOTAL VFA - Haryono, Yogo; nurhaita, Nurhaita (Jurnal Inspirasi Peternakan, 2023)
This study aims to evaluate the use of jengkol peel pellets in sheep rations and their effect on pH and total VFA. This research was conducted in May - July 2019 at the Block B Field Laboratory, Department of Nutrition and Feed Technology, Faculty of Animal Husbandry, Bogor Agricultural University (IPB). This study used a randomized block design (RBD) with 3 treatments and 5 replications. The treatments used were P1 = Concentrate (40%) + Field Grass (60%), P2 = Concentrate (40%) + Field Grass (45%) + Jengkol Peel (15%), P3 = Concentrate (40%) + Grass Field (37.5%) + Jengkol peel (22.5%). The results showed that the addition of 15% and 22.5% jengkol peel pellets containing tannins and saponins had no significant effect (P> 0.05) on pH, it is still under normal conditions, but decreases (P <0.01) at total VFA production. The total VFA production averaged 68.90 - 103.23 mM, decreased in the range of 19.90% - 33.26%. It can be concluded that the use of jengkol peel pellets in sheep rations does not affect pH and can reduce total VFA production, the best level of use is at the level of 15% jengkol peel pellets. Keywords: Jengkol Peel Pellets, Tannins, Saponins, Sheep, pH and Total VFA